Improving μ-wire electro-discharge machining operation of polished silicon wafer by conductive coating - Rasheed, Aous Naji; Abdul Muthalif, Asan Gani; Saleh, Tanveer (2014)
Micro-Wire Electro-discharge machining (-WEDM) is a nonconventional machining technology which is extensively used for metal based micro fabrication process. This is a non-contact machining process where material removal is taken place by electro-thermal action. -WEDM process is difficult to be applied for semiconductor material like Silicon (Si). In this paper a new approach is proposed for machining polished Si (p-type, resistivity 1-50 -cm) wafer. In this method, initially Si workpiece is coated with a conductive material (gold for this study) and then -WEDM operation is carried out. Finally, after WEDM operation, the conductive layer is removed from the polished Si substrate without damaging the substrate. WEDM process stability was found to be improved (up to 60 times for certain machining condition) if coated Si wafer is used as compared to uncoated Si workpiece. Material removal rate was also found to be increased by a good margin (~ 100% maximum) for coated Si wafer. Overall this new method of -WEDM operation of polished Si wafer has been found to be more efficient and useful.